Very late stent expansion with intracoronary lithotripsy: a case report. Issue 5 (17th October 2020) - Demarchi, Andrea; Ugo, Fabrizio; Cavallino, Chiara; Rametta, Francesco
Abstract: Background: Underexpanded stent in heavily calcified coronary lesion is common and persists over years. It is related to long-term failure and negative outcomes. Treatment of this situation after many years with intracoronary lithotripsy (ICL-Shockwave ® ) could be an option. Case summary: We report a case of a man with underexpanded coronary stent implanted 11 years earlier. Optical coherence tomography highlighted the mechanism of stent underexpansion showing the presence of calcium stones under the old struts. Intracoronary lithotripsy crushed calcium under the stent struts causing its geometric change (from elliptical to round shape) and a consequent better transmission of the true radial force of the old stent. Discussion: Heavily calcified coronary lesions lead to stent underexpansion which persists over years. Intracoronary lithotripsy could be a very late option to manage this unfavourable common result.